Kepuasan Konsumen: Faktor-Faktor Yang Mempengaruhi - Marlina Kurnia; Mr Suwiknyo (UMSurabaya Publishing, 2018)
ABSTRACT This article investigates the influence of brand awareness, perceived quality, brand association, brand loyalty, tangible, reliability, responsiveness, assurance, empathy customer satisfaction. The population is the customer in BPR Meru Sankara, the sample is taken with convinience with slovin method. Using sample 96 and tested using SPSS software. The results of this study show Perception Quality, Reliability, Responsiveness and Empatimiliki influence and significant to Customer Satisfaction. Thus the proposed hypothesis proves true. As for Brand Awareness, Brand Associations, Brand Loyalty, Physical Evidence and Guarantee no effect on Customer Satisfaction so that the hypothesis proposed is not proven. Further research is expected to add variable motivation and corporate culture in researching customer satisfaction.Keywords : Brand Quality, Sistem Quality, customer satisfactionCorrespondence to : marlinakurnia@ummgl.ac.id ABSTRAK Penelitian ini ingin mengetahui faktor yang memepengaruhi kepuasan konsumen, seperti brand awareness, perceived quality, brand association, brand loyalty, tangible, reliability, responsiveness, assurance, empathy. Populasi dalam penelitian ini adalah nasabah BPR Meru Sankara, denagn teknik pengambilan sample dengan accidental sampling. Sampel yang digunakan adalah 96 dan diolah menggunakan SPSS software.Hasil dari penelitian ini menjelaskan hubungan antara Perception Quality, Reliability, Responsiveness dan Empatimemiliki pengaruh pada kepuasan pelanggan.Sedangkan hubungan antara Brand Awareness, Brand Associations, Brand Loyalty, Physical Evidence dan Guarantee tidak memiliki pengaruh pada Customer Satisfaction . Penelitian selanjutnya diharapkan dapat menambah variabel yang diteliti yaitu motivasi dan kepuasan pelanggan.Kata kunci : Brand Quality, Sistem Quality, customer satisfactionKorespondensi : marlinakurnia@ummgl.ac.id